The network of voices: An analysis of the public ombudsman's office through the lens of actor-network theory (Research, Society and Development, 2026)
This essay analyzes the performance of the Public Ombudsman's Office as a sociotechnical phenomenon, utilizing the theoretical lenses of Actor-Network Theory. The objective is to investigate how citizen participation is actualized through heterogeneous associations between human and non-human actors; thus, by shifting the focus from traditional bureaucratic structures to the agency of objects, this work describes the ombudsman's office as a dynamic "hybrid collective," where analysts, citizens, legislation (Law No. 13,460/2017, LAI, and LGPD), registration systems (Fala.BR), and other infrastructures operate as interdependent actants. Methodologically, the study employs document analysis and the concept of translation to trace the trajectory of a manifestation, from its initial registration to its conversion into a management report (immutable mobile). The discussions reveal that the effectiveness of the ombudsman's office and the democratization of institutions depend not only on political will but on the robustness of technical and normative connections that allow the citizen's voice to circulate. It is concluded that citizen participation is an emergent property of the network, requiring an engineering of symmetric connections that sustains the flow of translation and transparency between the State and society.